Aplica????es de instrumentos para avalia????o da seguran??a do paciente ambulatorial quanto ao uso de medicamentos - Soares, V??vian Elaine Alflen (2019)
There is a considerable diversity in outpatient settings, especially those related to health care assistance. It is necessary to understand medication errors and adverse events to have a whole concept of patient safety. The main objective of this research was to detect the main patient safety flaws related to outpatient drug use in the public service. This is a prospective and exploratory cross-sectional case study with a quantitative and qualitative approach. We reviewed the literature available and we have chosen from the existing questionnaires a group of questions related to drugs and patient safety. Data collection was performed to apply the adapted questionnaire at the Universidade Nove de Julho multidisciplinary clinic. Study population was composed by 207 participants, with a mean age of 59.7 years, 64.9% are female and, 47.8% of participants completed high school. Most common diagnoses were systemic arterial hypertension and diabetes. Thyroid disorders, hypercholesterolemia, gastritis and other diseases have also been identified. Number of consultations was of 7.9 / patient (SD= 6.7), on average, 140 (67.6%) participants had been using the service for over a year, 150 (72.5%) of patients had already used medications. Medication have been used for 71.5 (?? 70.5) months. Two diseases were diagnosed in 34.8% of patients evaluated and, 2.4 drugs per patient were prescribed on average. In this study 97 (46.8%) of patients has forgotten to take the drugs prescribed at least once. Analgesics and antinflammatory were the most used drugs in this research. Seventy-six patients (36.7%) failed to comply with medication administration at the pre-established schedule and, 49 (23.7%) patients did not fully adhere to the recommended dosing. In the study population, 25 (12%) reported having had a drug-related adverse event. Furthermore, in 129 (62,3%) preventable drug-related adverse events were associated with errors in patient compliance. In conclusion, the questionnaire applied at multidisciplinary clinic brought sensitive information regarding medication in outclinic setting. We emphasize the importance of disseminate knowledge on medication to health professionals and patients contributing to the broadened view of appropriate practices to improve treatment adherence, to reduce adverse events related to medication and to promote better quality of life of patients.